Histórias (não) contadas : o acervo de arte popular do Centro Cultural São Francisco e a potência dos folguedos - Gomes, Raisa Filgueira Soares (2023)
In the ancient Saint Anthony Covent premises, located in the city of João Pessoa/ Paraíba, today known as the Saint Francis Cultural Center, there is a folk-art collection from Exposition Brazil, Popular Art Today, that originally took place in the late 80’s, together with the popular art archive from Federal University of Paraíba (UFPB), which was curated by the anthropologist, writer, and museologist Lélia Coelho Frota. Several kinds of art typologies were presented in this collection as well as artworks from all around Brazil, such as woodcuttings, ceramic, indigenous and afro-Brazilian art, ex-votos, among others. The rest of typologies presented countless other themes like popular feastings or folk plays from Northeast of Brazil, like “Cavalo Marinho” (Seahorse), “Reisado” and “Boi de Reis”, artistic expressions and acting that tells stories using dance, music, and scenic rituals. Thereby, the research has as objective to study the Saint Francis Cultural popular art archive in a perspective of connection between artists and their work within those popular feastings and the possibilities of cultural expression for beyond the old Saint Anthony Covent. Thus, this research’s specific objectives are to narrate the curatorship ramifications of the Saint Francis Cultural Center popular art archive, originally from Brazil Exposition, Popular Art Today, in order to reveal its untold history from the standpoint of the archive as a whole, even though, focusing on the popular feasts and folk play shown in in the archive and exposition; To show a living popular art in the street folk plays, using as tools the images from the archive itself that still keep a link with nowadays street feastings happening in Paraíba, cultural expression that breaks down the material boundaries of a museum made by stone and lime to reveal powerful and vivid artistic traditions.